2009
DOI: 10.1111/j.1365-2141.2009.07743.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible lower rate of chronic ITP after IVIG for acute childhood ITP an analysis from registry I of the Intercontinental Cooperative ITP Study Group (ICIS)

Abstract: SummaryIn children, one‐third of immune thrombocytopenic purpura (ITP) patients follow a chronic course. The present study investigated whether treatment with intravenous immunoglobulin (IVIG) at the time of diagnosis of ITP is of prognostic significance, using data from 1984 children entered in Registry I of the Intercontinental Cooperative ITP Study Group. A matched pairs analysis compared children with thrombocytopenia (platelet count <150 × 109/l) 6 months following diagnosis with children whose platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 24 publications
2
52
2
Order By: Relevance
“…Figure 5). 19,22,26,27,[30][31][32]37,44,46,[48][49][50] No significant differences were found. Fourteen studies analyzed the influence of treatment with IVIg and found significantly less chronic ITP in patients treated with IVIg (OR 0.71, 95% CI 0.52-0.97) ( Figure 5).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 5). 19,22,26,27,[30][31][32]37,44,46,[48][49][50] No significant differences were found. Fourteen studies analyzed the influence of treatment with IVIg and found significantly less chronic ITP in patients treated with IVIg (OR 0.71, 95% CI 0.52-0.97) ( Figure 5).…”
mentioning
confidence: 74%
“…The mean platelet count at time of diagnosis was calculated in 12 studies. 19,20,23,24,26,27,29,30,37,[41][42][43] A significantly higher platelet count at diagnosis was found in patients who developed chronic ITP, with a mean difference 5.27 (95% CI 2.69-7.86). Four articles calculated a median platelet count, and 1 found significantly higher median platelet counts at diagnosis in patients who developed chronic ITP.…”
mentioning
confidence: 99%
“…Estimates of ITP incidence range between 2 and 5 cases per 100 000 per year in children who are younger than 15 years old [4][5][6]; prevalence estimates range between 4.1 and 12.6 cases per 100 000, depending on age, with a mean prevalence of approximately 7.2 cases per 100 000 in children younger than 18 years old [7][8]. Approximately 75% of pediatric ITP cases are newly diagnosed and persistent, with the remaining cases considered chronic [9][10][11][12]. ITP in children is often associated with an antecedent illness or infection and often resolves within 1-6 months [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The most common initial therapies for pediatric ITP include intravenous immunoglobulin (IVIg), corticosteroids, or both [12,27]. Subsequent treatments include corticosteroids, corticosteroids with high-dose IVIg, IV Rho(D) Ig, immunosuppressive agents, and rituximab [3,28].…”
Section: Introductionmentioning
confidence: 99%
“…There are two lines of evidence. Firstly, recent analysis of the Intercontinental Registry Data suggests that children initially treated with IVIG were more likely to have a normal platelet count at 6 months from diagnosis than those not receiving it [5]. Secondly, the use of pulses of high-dose dexamethasone in two pilot studies in adults [6] (40 mg daily for 4 days every 14 or 28 days for four to six cycles) suggest a higher rate and a longer duration of remission, and this is now being tested in a prospective randomised study.…”
Section: Introductionmentioning
confidence: 99%